2022
DOI: 10.3390/molecules27144523
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects and Mechanisms of Berberine from Medicinal Herbs: An Update Review

Abstract: Cancer has been a serious public health problem. Berberine is a famous natural compound from medicinal herbs and shows many bioactivities, such as antioxidant, anti-inflammatory, antidiabetic, anti-obesity, and antimicrobial activities. In addition, berberine shows anticancer effects on a variety of cancers, such as breast, lung, gastric, liver, colorectal, ovarian, cervical, and prostate cancers. The underlying mechanisms of action include inhibiting cancer cell proliferation, suppressing metastasis, inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 133 publications
3
19
0
Order By: Relevance
“…Berberine is an isoquinoline alkaloid [23]. Studies have shown that Berberine has a good broad-spectrum antibacterial effect and can inhibit bacteria as well as having strong anti-inflammatory and some immunomodulatory effects [24,25].…”
Section: Discussion:mentioning
confidence: 99%
“…Berberine is an isoquinoline alkaloid [23]. Studies have shown that Berberine has a good broad-spectrum antibacterial effect and can inhibit bacteria as well as having strong anti-inflammatory and some immunomodulatory effects [24,25].…”
Section: Discussion:mentioning
confidence: 99%
“…In addition to breast cancer and glioblastoma, BBR has shown promising effects on other types of cancers, such as lung, gastric, liver, ovarian, colorectal, cervical, prostate, pancreatic bladder, endometrial, and esophageal cancers. The common mechanisms of action of BBR on cancer involve primarily inhibiting inflammation, suppressing cell proliferation and migration/metastasis, arresting cell cycle, and inducing apoptosis [98].…”
Section: Effect Of Berberine On Apoptosis and Necrosis Of Transformed...mentioning
confidence: 99%
“…Furthermore, low dose of curcumin treatment could exert anxiolytic effect through improving the synaptic plasticity to enhance neural circuits, but high dose of curcumin reversed anxiolytic effect because of inducing neuroinflammation to affect hippocampal neurogenesis [ 131 ]. This also could be because antioxidants with low dose would show antioxidant activity in vivo, but they with high dose would exhibit pro-oxidative activity in vivo [ 132 , 133 , 134 ]. Additionally, in a cadmium-exposed mouse model, curcumin decreased anxiety-like behaviors by promoting the production of viable prefrontal cortex neuronal cells, and suppressing neuroinflammation in prefrontal cortex [ 135 ].…”
Section: Anxietymentioning
confidence: 99%